Efektivitas dan Tantangan Pemilihan Kepala Desa Secara E-Voting di Kabupaten Magetan - Dwi Irawan, Bayu; Ratih Wulandari, Florentina; Kismartini, Kismartini (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This research is motivated by the decrease in community participation in the election of village heads (Pilkades) by e-Voting in Magetan Regency in 2023 compared to 2019. The purpose of this study is to analyze the effectiveness, identify challenges and supports for the implementation of e-Voting in the Regional Elections in Magetan Regency. The research method used is a qualitative approach with data collection techniques through interviews using the snowball sampling method on informants from the Community and Village Empowerment Office, Communication and Information Service, Village Government, Pilkades committee, and the elderly. Data is also obtained from archives, reports, regulations, and technical instructions related to the implementation of e-Voting. Data analysis techniques include data condensation, data presentation, and conclusion drawn. The results of the study show that the implementation of e-Voting in Magetan Regency in general has been effective by being marked by the achievement of the objectives of the activity. Challenges faced include: limited technological infrastructure, low digital literacy, system reliability and technical failures. The challenges of implementing e-Voting can be overcome with collaboration and synergy across agencies and election committees. Collaboration and synergy in the implementation of e-Voting is supported by strong organizational characteristics, a supportive environment, competent human resources, and progressive policies and management. The research recommendations include increasing socialization through online and offline media in a balanced manner, developing e-Voting applications independently, and appointing special staff to support the sustainability of e-Voting innovation.